2022
DOI: 10.3389/fpls.2022.997557
|View full text |Cite
|
Sign up to set email alerts
|

Integrated proteomics and metabolomics analysis of rice leaves in response to rice straw return

Abstract: Straw return is crucial for the sustainable development of rice planting, but no consistent results were observed for the effect of straw return on rice growth. To investigate the response of rice leaves to rice straw return in Northeast China, two treatments were set, no straw return (S0) and rice straw return (SR). We analyzed the physiological index of rice leaves and measured differentially expressed proteins (DEPs) and differentially expressed metabolites (DEMs) levels in rice leaves by the use of proteom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…Sakit et al (2022) found that the leachate extract of Acacia saligna decreased photosynthesis, PSII activity, and water use efficiency of tested crop species, with evident effects at higher concentrations. Yan et al (2022) found that the straw return treatment could reduce the photosynthetic capacity, inhibiting the growth of rice plants. Kumar and Singh (2018) found higher amounts of CAT and SOD in insect-damaged Ludwigia species compared to undamaged plants.…”
Section: Discussionmentioning
confidence: 99%
“…Sakit et al (2022) found that the leachate extract of Acacia saligna decreased photosynthesis, PSII activity, and water use efficiency of tested crop species, with evident effects at higher concentrations. Yan et al (2022) found that the straw return treatment could reduce the photosynthetic capacity, inhibiting the growth of rice plants. Kumar and Singh (2018) found higher amounts of CAT and SOD in insect-damaged Ludwigia species compared to undamaged plants.…”
Section: Discussionmentioning
confidence: 99%
“…Untargeted metabolomics allows a good understanding of changes in metabolism due to stress at the tissue level in real time. In addition, most of the rice metabolomic studies have focused on leaves, while plants encounter salt stress first in the root (Lawas et al., 2019 ; Yan et al., 2022 ). We performed comparative untargeted/global metabolomics using root tissues of salt‐sensitive O. sativa and highly salt‐tolerant O. coarctata under control (0 mM NaCl) and saline (120 mM NaCl) conditions to reduce the gap in the knowledge of root‐specific adjustments in metabolites which help or hinder the plant to survive as it encounters abnormal salt levels.…”
Section: Introductionmentioning
confidence: 99%